In vitro digestion analysis of soft candy containing peptide-zinc chelates derived from low-fluoride protein hydrolysates of Antarctic krill (Euphausia superba) powder - Qinguo Quan; Hongwu Ji; Ming Chen; Zewei Zhang (Future Foods, 2024)
This study developed a soft candy with peptide-zinc chelates using low-fluorine protein hydrolysates derived from Antarctic krill powder. To achieve this, the enzymatic hydrolysis conditions of the protein isolates were optimized through single-factor experiments. Protein hydrolysates were used to produce Antarctic krill peptides (AKP) through ceramic membrane microfiltration at various pressure levels. AKP-zinc chelates (AKP-Zn) were prepared by mixing AKP and zinc sulfate, subsequent to characterized the resulting complex. Finally, we examined the tolerance of AKP-Zn and soft candy containing AKP-Zn (SC-AKP-Zn) to simulated gastrointestinal digestion in vitro. The optimal enzyme mix was a 1:1 ratio of alkaline and flavored protease, with 4000 U/g enzymes, pH 7.5 and 3 h, and the ceramic membrane microfiltration increased the protein content in AKP by approximately 85.34 ± 3.54 %. Characterization showed that AKP effectively interacts zinc ions through bonding with oxygen and nitrogen atoms, helps the strength of AKP-Zn in various pH levels and simulated digestive systems. AKP-Zn and SC-AKP-Zn showed higher bioavailability compared to zinc sulfate and zinc gluconate. These results provide a solid theoretical foundation for creating ready-to-eat food products with AKP-Zn and offer new insights into the potential applications of Antarctic krill proteins.